Patterns of Orbital Fracture and Association with Other Mid Face Fractures: A Retrospective Study (Medical Forum Monthly, 2024)
Introduction: Orbital fractures are among the most frequent of the middle facial injuries. Orbital fractures are seen as an isolated orbital floor or wall fracture, or as a part of middle facial injuries. Trauma severity ranges from isolated orbital floor or wall fractures to a degree of distruption that involves other middle facial fractures which require immediate surgical intervention.Objective: To analyze the pattern of orbital floor fractures and association with other mid face fractures.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at Oral and Maxillofacial surgery department Liaquat University hospital Hyderabad from January 2012 to December 2012Materials and Methods: 257 patients, who had sustained middle facial bone fractures were included. Data collected included age, gender, pattern of orbital fractures and its association with other middle facial injuries. Data was collected through records of patient’s clinical examination and imaging investigations e.g. Plain radiographs OPG, P.A View of face, occipitomental view and CT scan if necessary . Data was analysed by SPSS 17 software.Results: In this one year study, we received 257 patients of middle facial trauma, out of those 257 patients 78 cases (30.35%) involved orbital fractures. Orbital floor with lateral wall (39.74%) was the most susceptible pattern of fracture followed by lateral wall (26.64%) fractures & orbital floor fracture with medial wall involvement (14.10%). Zygomatico-maxillary complex fracture (62.82%) was the most commonly associated with orbital fractures among other middle facial injuries followed by Lefort III (35.41%).Conclusion: Orbital fractures should be considered during examination of trauma patients especially in case of middle facial injuries. . It is suggested that all cases of middle facial injuries associated with orbital fractures should have an immediate diagnosis and early management to decrease the complications.